2018
DOI: 10.1371/journal.pone.0204051
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of plasma microRNAs and their roles in diagnosis of mild to severe traumatic brain injury

Abstract: Traumatic brain injury (TBI) is associated with trauma-related death. In this study, we evaluated differences in the expression of plasma microRNAs (miRNAs) in patients with different degrees of TBI, and explored the potential of miRNAs for use as diagnostic TBI biomarkers. The miRNA microarray results showed upregulation of 65, 33, and 16 miRNAs and downregulation of 29, 27, and 6 miRNAs in patients with mild, moderate, and severe TBI, respectively, compared with healthy controls. Thirteen miRNAs (seven upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 55 publications
(50 reference statements)
0
32
0
Order By: Relevance
“…Redell and colleagues implemented miRNA microarrays and found significant changes in the levels of miR‐16, miR‐92a, and miR‐765 in plasma after TBI, demonstrating that circulating miRNAs are altered after TBI (Redell et al ). Bhomia et al () found that the identified 10 serum miRNAs can be used for the diagnosis of mild and moderate TBI as well as sTBI, Recently, Qin et al () screened and confirmed that miRNAs were potential biomarkers for the diagnosis and prognosis of TBI using miRNA microarrays. However, a limited number of TBI patients were included in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redell and colleagues implemented miRNA microarrays and found significant changes in the levels of miR‐16, miR‐92a, and miR‐765 in plasma after TBI, demonstrating that circulating miRNAs are altered after TBI (Redell et al ). Bhomia et al () found that the identified 10 serum miRNAs can be used for the diagnosis of mild and moderate TBI as well as sTBI, Recently, Qin et al () screened and confirmed that miRNAs were potential biomarkers for the diagnosis and prognosis of TBI using miRNA microarrays. However, a limited number of TBI patients were included in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether these potential biomarkers play a role in the pathological process of the nervous system is still rarely reported. Moreover, most existing studies are either based on a limited number of patients, only focus on a few specific miRNAs or provide no prognostic results, which may partially explain some of the discrepancies observed (Redell et al ; Bhomia et al ; Yang et al ; Qin et al ). Recently, Di Pietro et al () screened miRNAs and validated that they were potential biomarkers for the diagnosis and prognosis of TBI using TaqMan Low Density Array (TLDA).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental strategy employed in this investigation has several distinct advantages over those employed in the small number of large-scale miRNA biomarker discovery analyses performed in TBI to date. Most notably, PREPRINT 6 prior investigations have identified candidate miRNAs by high-throughput comparisons of circulating miRNAs between TBI patients and healthy controls [20,[24][25][26]. Thus, it is unclear whether the miRNAs identified in these studies exhibit elevation in blood which are specific to brain injury, or just trauma in general.…”
Section: Discussionmentioning
confidence: 99%
“…TBI regulates brain miRNA expression acutely [14][15][16][17], and some miRNAs remain regulated chronically-months to years after TBI [18,19]. Dysregulated miRNA levels are reported in the cortex [9,14,[20][21][22], hippocampus [15,16,18,19,[23][24][25][26][27], and plasma [28][29][30]. Only a few studies, however, have addressed miRNA expression in patients with TBI [13,19,23,28], highlighting the gap between preclinical and clinical studies.…”
mentioning
confidence: 99%
“…Dysregulated miRNA levels are reported in the cortex [9,14,[20][21][22], hippocampus [15,16,18,19,[23][24][25][26][27], and plasma [28][29][30]. Only a few studies, however, have addressed miRNA expression in patients with TBI [13,19,23,28], highlighting the gap between preclinical and clinical studies. Our previous study showed that TBI results in miR-124-3p downregulation in both rat and human dentate gyrus, making this miRNA an interesting subject for further study.miR-124 is the most abundant microRNA in the brain, accounting for 25-48% of all brain miRNA pool [31].…”
mentioning
confidence: 99%